Engineering of Chinese Hamster Ovary Cells With NDPK-A to Enhance DNA Nuclear Delivery Combined With EBNA1 Plasmid Maintenance Gives Improved Exogenous Transient Reporter, mAb and SARS-CoV-2 Spike Protein Expression - Budge, James D.; Young, Robert J.; Smales, Christopher Mark (Frontiers in Bioengineering and Biotechnology, 2021)
Transient gene expression (TGE) in mammalian cells is a method of rapidly generating recombinant protein material for initial characterization studies that does not require time-consuming processes associated with stable cell line construction. High TGE yields are heavily dependent on efficient delivery of plasmid DNA across both the plasma and nuclear membranes. Here, we harness the protein nucleoside diphosphate kinase (NDPK-A) that contains a nuclear localisation sequence (NLS) to enhance DNA delivery into the nucleus of CHO cells. We show that co-expression of NDPK-A during transient expression results in improved transfection efficiency in CHO cells, presumably due to enhanced transportation of plasmid DNA into the nucleus via the nuclear pore complex. Furthermore, introduction of the Epstein Barr Nuclear Antigen-1 (EBNA-1), a protein that is capable of inducing extrachromosomal maintenance, when coupled with complementary oriP elements on a transient plasmid, was utilised to reduce the effect of plasmid dilution. Whilst there was attenuated growth upon introduction of the EBNA-1 system into CHO cells, when both NDPK-A nuclear import and EBNA-1 mediated technologies were employed together this resulted in enhanced transient recombinant protein yields superior to those generated using either approach independently, including when expressing the complex SARS-CoV-2 spike (S) glycoprotein.